Strategy professionals: strategic planners and strategy consultants - Whittington, Richard (Henry Stewart Talks, 2012)
The strategy profession, Strategic planners and strategy consultants, Demand for strategy professionals, Why the strategy profession matters, Nature of the strategy profession, Four forces shaping the strategy profession, Open strategy, Issues for research